Job insecurity and life courses / Sonia Bertolini, Valentina Goglio and Dirk Hofäcker. - Bertolini, Sonia; Goglio, Valentina; Hofäcker, Dirk (Bristol University Press, 2024)
Drawing from interviews and survey data across the EU and the UK, this in-depth study explores how worker instability is perceived and experienced, and how this 'perception' in turn affects individuals' economic and social situation. Using intersectional analysis, the authors identify groups who are more prone to labour market risks.